2017
DOI: 10.1186/s12915-017-0351-0
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics reveals that an anthropophilic population of Aedes aegypti mosquitoes in West Africa recently gave rise to American and Asian populations of this major disease vector

Abstract: BackgroundThe mosquito Aedes aegypti is the main vector of dengue, Zika, chikungunya and yellow fever viruses. This major disease vector is thought to have arisen when the African subspecies Ae. aegypti formosus evolved from being zoophilic and living in forest habitats into a form that specialises on humans and resides near human population centres. The resulting domestic subspecies, Ae. aegypti aegypti, is found throughout the tropics and largely blood-feeds on humans.ResultsTo understand this transition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
140
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(154 citation statements)
references
References 67 publications
14
140
0
Order By: Relevance
“…A recent study (Crawford et al., ) based on exome sequence data, suggested that Aaa may have arisen from populations of Aaf in West Africa, specifically from Senegal which was the only West African country sampled in that study. Our data indicate that, while Senegal has some genetic signal typical of Aaa outside Africa, the Angola sample displays an even stronger signal of genetic relatedness to Aaa outside Africa (Figure ).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A recent study (Crawford et al., ) based on exome sequence data, suggested that Aaa may have arisen from populations of Aaf in West Africa, specifically from Senegal which was the only West African country sampled in that study. Our data indicate that, while Senegal has some genetic signal typical of Aaa outside Africa, the Angola sample displays an even stronger signal of genetic relatedness to Aaa outside Africa (Figure ).…”
Section: Discussionmentioning
confidence: 85%
“…However, there is a major difference between Bennett et al A recent study (Crawford et al, 2017) based on exome sequence data, suggested that Aaa may have arisen from populations of Aaf in West Africa, specifically from Senegal which was the only West…”
Section: Ta B L E 3 Population Differentiationmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent evidence based on the sequencing of DNA and nucleotide polymorphisms (SNPs) of Aedes aegypti supports the evidence that shows that mosquito populations in the New World are derived directly from African populations. A. aegypti originated in Africa and then colonized the Americas, Oceania and the Asian tropics through trade during the 17thÀ19th centuries (Powell and Tabachnick, 2013;Brown et al, 2011;Brown et al, 2014;Bennett et al, 2016;Crawford et al, 2017). This redistribution of A. aegypti coincided with the appearance of yellow fever and dengue fever in the Americas and dengue fever in Asia (Gould et al, 2003;Tabachnick, 1991;Urdaneta-Marquez and Failloux, 2011).…”
Section: Relations Between Viruses and Insectsmentioning
confidence: 99%
“…aegypti have shown that the ancestral African populations are genetically distinct from a more domesticated pantropical form of Ae. aegypti that is widespread throughout the Tropics (Bennett et al., ; Brown, McBride, et al., , ; Crawford et al., ; Gloria‐Soria et al., ). Inference of the demographic history of Ae.…”
Section: Introductionmentioning
confidence: 99%